THE TARGET ACCURACY OF THE PAK TUAH PROGRAMME AS A MEASURE OF THE EFFECTIVENESS OF POPULATION ADMINISTRATION SERVICES IN PESAWARAN REGENCY - Khansa Dewinta Kusuma; Simon Sumanjoyo Hutagalung; Ita Prihantika (Jurnal Honai, 2026)
Public services are an essential aspect in meeting society’s needs related to administration and daily activities. Effective services, particularly in the governmental sector, have become a public demand in obtaining fast, accessible, and high-quality services. The Department of Population and Civil Registration of Pesawaran Regency, as the agency responsible for population administration services, strives to improve service quality through an outreach-based innovation called the Pak Tuah Program. This program aims to bring services closer to the community and accelerate the issuance of population documents directly at residents’ locations This study aims to determine the effectiveness of the Pak Tuah Program in providing population administration services in Pesawaran Regency. The research method used is descriptive quantitative, referring to the program effectiveness theory by Sutrisno (2007). The results show that the Pak Tuah Program is categorized as effective with a mean score of 3.24. This indicates that the community understands the program’s objectives, experiences ease of service, and receives direct benefits. The program has also improved public access and service quality. However, the timeliness indicator remains an obstacle as some processes are not yet in accordance with the schedule. Therefore, increased coordination, time management, and continuous evaluation are needed to achieve more optimal results in the future.